2019
DOI: 10.1155/2019/2163838
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Genistein Could Modulate Hypothalamic Circadian Entrainment, Reduce Body Weight, and Improve Glucose and Lipid Metabolism in Female Mice

Abstract: Genistein has beneficial effects on metabolic disorders. However, the specific mechanism is not clearly understood. In light of the significant role of the hypothalamus in energy and metabolic homeostasis, this study was designed to explore whether dietary genistein intake could mitigate the harmful effects of a high-fat diet on glucose and lipid metabolism and whether any alterations caused by dietary genistein were associated with hypothalamic gene expression profiles. C57BL/6 female mice were fed a high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Genistein demonstrated an inhibitory effect on tyrosine kinase which dysregulates glucose homeostasis (Figure 3) [199]. The administration of genistein to mice reduced body weight and improved glucose and lipid metabolism [200]. A transcriptome analysis revealed that genistein could affect the regulation of the hypothalamic circadian rhythms which could provide a novel target for the therapy of diabetes and obesity.…”
Section: Anti-diabetic Effects Of Selected Flavonoidsmentioning
confidence: 99%
“…Genistein demonstrated an inhibitory effect on tyrosine kinase which dysregulates glucose homeostasis (Figure 3) [199]. The administration of genistein to mice reduced body weight and improved glucose and lipid metabolism [200]. A transcriptome analysis revealed that genistein could affect the regulation of the hypothalamic circadian rhythms which could provide a novel target for the therapy of diabetes and obesity.…”
Section: Anti-diabetic Effects Of Selected Flavonoidsmentioning
confidence: 99%
“…The serum insulin concentrations, total cholesterol (TC), triacylglycerol (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and free fatty acids (FFA) were measured as previously described. 22 Insulin sensitivity was assessed using the homeostasis model assessment of insulin resistance (HOMA-IR). The HOMA-IR was calculated as previously described.…”
Section: Serum Biochemical Parameter Measurementmentioning
confidence: 99%
“…Genistein, the most abundant isoflavone in soy, is metabolized by gut bacteria into numerous metabolites [16] that target and modulate estrogen-dependent and non-estrogenic activity pathways with a wide variety of biological activities (e.g., the reduction of inflammation) [17][18][19][20]. Recently, genistein has been highlighted to have the capacity to reduce inflammation, modify adipocyte functioning, and maintain body weight [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%